GENREAL CHARACTERISTICS OF UZBEK CHILDREN'S STORIES (ON THE EXAMPLE OF A. OBIDJON'S STORY "GULIKHON'S FLOWER PLANT") (Scientific journal of the Fergana State University, 2023)
Methodological pecularites of Hestories for children written by Anvar Abidjan   are analyzed  in this article.  Skills and abilities defended on the writer were explained and completely opened